STUDI KASUS PEMENUHAN BERSIHAN JALAN NAFAS PADA PASIEN TB PARU DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN TAHUN 2018 - Deni Susyanti; Mompang Tua Parlagutan; Susiana Marbun (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Background of pulmonary tuberculosis is an infective disease caused by a microbacterium tuberculosis basil which is one of the breathing diseases under parts most tuberculosis bacilli enter the lung tissue through airbone infection and then undergo a process known as the primary focus of ghon. The main symptoms of pulmonary tuberculosis are coughing for two weeks or more, cough accompanied by phlegm, sputum mixed with blood, difficulty breathing, weakness, loss of appetite, weight loss. One of the signs and symptoms of tuberculosis are coughing accompanied by phlegm and will lead to the ineffectiveness of the respiratory tract hygiene is not effective. Effective coughing is a nursing activity to clear secretions in the airway, which serves to improve secretion mobilization and prevent high risk of retention of secretions. After being given an effective cough action within 1 x 24 hours, the patient is expected to experience an increase in airway clearance in pulmonary TB patients at the Second Putri Hijau Hospital in Medan. The design of this study was a descriptive study with 2 pulmonary TB patients at the Second Putri Hijau Hospital in Medan. The results obtained from the two respondents in patients with pulmonary TB that fulfillment of airway clearance is met, but the time is different because the age is different from the two respondents. From the above studies it can be concluded that teaching coughs can effectively increase secretion mobilization. The advice from researchers is to always pay attention to the treatment program by always monitoring and evaluating the actions of teaching effective cough to patients with pulmonary TB.Keywords: pulmonary tuberculosis, respiratory hygiene, effective cough